PENGARUH FINANCIAL DISTRESS, AUDIT TENURE, DAN DIVIDEND POLICY TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN SERTA PENGARUH TERHADAP AUDIT SWITCHING PADA SITUASI SEBELUM DAN SELAMA PANDEMI COVID-19 DI INDONESIA - VARIANTO, BRIAN TONI; IBRANI, EWING YUVISA (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2024)
This study aims to determine the influence of financial and non-financial factors on the acceptance of going concern audit opinions   with debt to equity ratio and market-to-book ratio as control variables in transportation companies listed on the Indonesia Stock Exchange in 2018-2022. This research is a type of quantitative research. The sampling method used was purposive sampling and 15 companies were selected. The analysis technique used is logistic regression analysis with SPSS software version 26. The results of this study show that financial distress has a significant negative effect on the going concern audit opinion, tenure audit and dividend policy have no effect on the going concern   audit opinion,   the debt to equity ratio control variable has an influence on the going concern   audit opinion,   the market-to-book ratio variableIt has no influence on the Going Concern audit opinion,   and   the Going Concern audit opinion has no effect on the switching auditor.